Correlation between Physical Activity Time Reported by the IPAQ and Accelerometer in Syrian Adults (Epidemiology, Biostatistics, and Public Health, 2024)
Background: The accelerometer and self-report questionnaires have been recommended as efficient methods to measure physical activity (PA). The aim of this work is to investigate issues associated with PA assessment using the ActiGraph WGT3X-BT (AG) accelerometer and the Syrian version of the International Physical Activity Questionnaire-short form (IPAQ-SF-SY) in adults living in Damascus city.Methods: A sample of 52 (age 18- 60 years) Syrian men (17) and women (35) in a cross-sectional study wore the AG accelerometer for seven days and completed the IPAQ-SF-SY on the seventh day. Total PA, time spends in standing and sitting assessed by IPAQ-SF-SY and AG accelerometer were compared.Results: The IPAQ-SF-SY overestimates PA time among Syrian adults. IPAQ-SF-SY reported more time of total PA [763(660) vs 607(149) min, p=0.003], vigorous PA [29(1) vs 1(0.2) min, p=0.524], moderate PA [94(76) vs 42(22) min, p=0.032], MVPA [122(106) vs 43(22) min, p=0.019], and significantly less sedentary time than AG accelerometer [447(180) vs 643(93) min, p=0.728], mean (SD) respectively. Some differences were noticed in the correlations by gender, age, BMI, education statues, and smoking for PA and sedentary behavior (SB). For all correlations, there were no significant differences between sub groups.Conclusions: Data suggest that it is important to improve the specificity and sensitivity of the IPAQ-SF-SY with Arabic-speaking subjects and further study is needed to approve the utilization of PA self-report in Arabic.
Keywords: Questionnaire; Self-report; Measurements; MVPA; acigraph; sitting time